Fluorescein‐guided intraoperative endoscopy in patients with hereditary hemorrhagic telangiectasia: first impressions. Issue 3 (11th November 2016) - Pagella, Fabio; Pusateri, Alessandro; Zaccari, Dario; Bongetta, Daniele; Zoia, Cesare; Spinozzi, Giuseppe; Olivieri, Carla; Matti, Elina
Abstract : Background: Hereditary hemorrhagic telangiectasia (HHT) is a rare genetic disease that results in mucocutaneous telangiectasias and arteriovenous visceral malformations. Nasal telangiectasias lead to recurrent epistaxis, which affects up to 96% of patients. Different morphologic classifications and methods of visualization of nasal lesions have been described in the literature. We developed a new method of intraoperative endoscopy based on the intravenous administration of fluorescein. Preliminary data of this technique are reported. Methods: After the intravenous administration of sodium fluorescein, an intraoperative fluorescein‐guided endoscopy was carried out using photographic customized yellow filters on top of a 0‐degree, 4‐mm endoscope. Results: In 2015, 65 HHT patients underwent surgery for their epistaxis in our institution, and in 7 patients (3 males, 4 females; mean age, 54 years) an intraoperative fluorescein‐guided intraoperative nasal endoscopy was performed. No adverse events or complications were observed. Conclusion: First impressions regarding the usage of this technique in HHT patients seem to be promising and positive in terms of efficacy and safety. However, further studies with larger cohorts of patients should be performed in order to better investigate the use of this method for diagnostic and surgical purposes in HHT.